Global Research Trends on C-Reactive Protein and Periodontitis: A Comprehensive Bibliometric Analysis - Ratre, Madhu Singh; Engla, Deepali; Mishra, Shivani; Kalburgi, Veena; Singh, Shivangi; Sawant, Mitisha Anant (Journal of Neonatal Surgery, 2025)
Introduction: Periodontitis is a chronic inflammatory disease which leads to the progressive destruction of periodontal tissues and is linked to elevated CRP levels in researches. This bibliometric analysis focuses on research landscape indexed in PubMed from 2004 to 2024. Methods: Articles were extracted from PubMed, and bibliometric data, including titles, authors, institutions, and keywords, were analysed using R programming and R Studio. The search strategy included terms related to periodontitis and CRP. Results: A total of 231 documents were identified, reflecting significant contributions from the University of Pisa and the University of Catania. Key journals included the Journal of Clinical Periodontology and the Journal of Periodontology. Prominent authors were D’Aiuto F, Orlandi M, and Offenbacher S. Conclusion: The study highlights the research on CRP and periodontitis, with notable contributions from leading researchers and institutions. It underscores the importance of CRP as a systemic inflammatory marker and its association with periodontitis.